2007
DOI: 10.1007/s10584-007-9257-0
|View full text |Cite
|
Sign up to set email alerts
|

Climate, stream flow prediction and water management in northeast Brazil: societal trends and forecast value

Abstract: We assess the potential benefits from innovative forecasts of the stream flows that replenish reservoirs in the semi-arid state of Ceará, Brazil. Such forecasts have many potential applications. In Ceará, they matter for both water-allocation and participatory-governance issues that echo global debates. Our qualitative analysis, based upon extensive fieldwork with farmers, agencies, politicians and other key actors in the water sector, stresses that forecast value changes as a society shifts. In the case of Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 48 publications
1
29
0
Order By: Relevance
“…Case studies in the US and around the world have shown that institutions and organizational culture matter to the usability of information (102,109,113,(126)(127)(128)(129)(130)(131)(132)(133). For example, research found that organizations with more flexible decision-making frameworks (66) and those that insulate technocratic decision makers (134) are more likely to use information.…”
Section: Producer-user Interactions and Decision Environmentsmentioning
confidence: 99%
“…Case studies in the US and around the world have shown that institutions and organizational culture matter to the usability of information (102,109,113,(126)(127)(128)(129)(130)(131)(132)(133). For example, research found that organizations with more flexible decision-making frameworks (66) and those that insulate technocratic decision makers (134) are more likely to use information.…”
Section: Producer-user Interactions and Decision Environmentsmentioning
confidence: 99%
“…Additionally, if certain actors have overriding power over decisions, many stakeholders can become disinterested in participating (Broad et al, 2007). In this research, like Rigg's study of herders (Robin Rigg, 2002), I found that farm workers influenced the degree of perceived livestock depredation experience on farms and were therefore important actors in carnivore conservation.…”
Section: Is Participation the Holy Grail Of Conservation Interventions?mentioning
confidence: 69%
“…Currently, however, there exists little evidence of direct forecast use in operations, especially in water resources management, even in regions of scarcity. This is often ascribed to water managers tendency to act in a risk averse manner, "poor" forecast skill or scale, difficulty in integrating forecasts into existing decision support systems, lack of focus on specific user needs, anticipated shifts in the water sector, management and political disincentives, individual and institutional inflexibility, behavioral effects, and informational constraints (Pulwarty and Redmond, 1997;Hamlet et al, 2002;Ritchie et al, 2004;Rayner et al, 2005;Broad et al, 2007;Johnston et al, 2007;Lemos, 2008;Millner, 2009;Ziervogel et al, 2010).…”
Section: Introductionmentioning
confidence: 99%